On the Methods of Designing the Early Byzantine Basilicas of Chersonesos - Zavadskaya, Irina A. (Actual Problems of Theory and History of Art, 2019)
The remains of eleven Early Byzantine basilicas were investigated in ancient Chersonesos(Cherson), the main center of Byzantine culture in Crimea. The article presents the results of studying their planned structure using a system of numerical proportions, which was elaborated by Hans Buchwald. The proportional features of the plans of nine basilicas of Chersonesos suggest that in their design three variants of the proportional system could have been used. They differ in the main proportions that form the plan of the naos (nave and aisles) and the basilica building as a whole.The first variant includes the basilicas with “elongated” proportions (West Basilica and Uvarov Basilica).Width and length of the church including inner narthex and apse are proportioned 1:2, nave and aisles together, 2:3. The distinctive feature of the Uvarov Basilica is the double width of the narthex; therefore, itis proportioned 1:2 including a half of the narthex. The basilicas with “medium” proportions (Basilica 1935,East Basilica and Basilica on the Hill) belong to the second variant. The churches including two narthexes and apse are proportioned 1:2, nave, aisles and apse together and nave, aisles and narthex together — 2:3.The third variant includes the basilicas with “shortened” proportions (Basilica in a Basilica, Basilica 1932,Basilica on Agora, and North Basilica). The whole basilica is proportioned 2:3, nave and aisles together, 1:1. Many proportions of some parts of buildings were common to basilicas of different variants. Most likely some basilicas were built on one project.The proportions and sometimes the dimensions of the Chersonesos basilicas have analogies among the monuments of Constantinople, Asia Minor and Balkan Peninsula. This means that their creators were well acquainted with the construction methods of these regions and applied them in local conditions.